(untitled) (Journal of Partial Differential Equations, 2020)
"In this paper we consider the Lam00e9 system on a polygonal convex domain with mixed boundary conditions of Dirichlet-Neumann type. An explicit L^2 norm estimate for the gradient of the solution of this problem is established. This leads to an explicit bound of the H^1 norm of this solution. Note that the obtained upper-bound is not optimal."